PENGEMBANGAN MEDIA BELAJAR BERBASIS ANDROID PADA MATERI TATA SURYA UNTUK SISWA SEKOLAH DASAR - Gunawan; Miftianul Khosiyah (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
The purpose of this study is to develop an android-based learning media of solar system for elementary school students, particularly in Grade 6. This study is a research and development (R & D). The research and development model used in this study is a 4-D model which is developed by Thiagarajan (1974). There are 4 stages in this model, namely Define, Design, Development and Dissemination. The result of the development of learning media in the form of an android application with the APK format. The assessment score of the material experts reaches an average of 4.38 which means "Very Good". The assessment score of media experts reaches an average of 4.45 which means "Very Good". Individual test results reaches an average of 4.72 which means "Very Good", while the results of field test reaches an average of 4.84 which means "Very Good".